Between Rivers and Oceans : Mapping Afro-Latin American Experiences of Transformation - Gruber, Valerie (VAD 2024 "Reconfigurations in Africa - and in African Studies" (Conference of the Association for African Studies in Germany), 2024)
Connecting creative movements of Black re-existence across the African diaspora is crucial to fight colonial and racist exclusion. However, this requires highly sensitive means and media to express bodily, emotional and spiritual experiences of transformation that can hardly be captured by logocentric approaches. Against this backdrop, the multimedia book “Todo Rio Resiste Mar: Cartografias de Memorias Afrolatinas” (dirs. Valerie V. V. Gruber and Gilbert Shang Ndi, Andarilha Edições 2023, https://doi.org/10.15495/EPub_UBT_00007702) presents illustrations, poems, memoirs, choreographic and music performances created by young Afrodescendant artists from marginalised communities in Salvador da Bahia (Brazil) and Cartagena de Indias (Colombia). The anthology is the result of an exchange programme carried out over four years based on transdisciplinary methods of participatory action research, social arts and research-creation. The design of the e-book follows the journey of a river returning to the ocean, meandering through complex social and cultural territories. The encounter of different waters and currents is more than just a metaphor; it is the conceptual ground for the understanding of Afro-Latin American re-existence, personal and collective overcoming as well as decolonial healing. This presentation invites the public to dive into the rhythms, memories and imaginations of the exchange participants, reorganized in a map-collage with strong audio-visual impulses. The diverse voices and representations will set afloat discussions on the ethics and aesthetics of Afro-Latin American struggles against colonialism and racism, while raising questions on the degree to which traumatic experiences can be transmitted and transformed through artistic means across time, space and power hierarchies.